Studi Fenomenologi Kesejahteraan Emosional Praktisi Tasawuf - Ilham Ramadhani Huda; Satrio Artha Priyatna (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study focuses on exploring the influence of Sufism practices on the emotional well-being of individuals in Indonesia. Sufism, as a mystical dimension of Islam, offers a spiritual approach through practices such as remembrance (dhikr), meditation, and self-reflection (muhasabah), aiming to cleanse the soul and draw closer to the Divine. The research employs a qualitative approach with a phenomenological design to delve into the subjective experiences of Sufi practitioners regarding their emotional well-being. The results indicate that these practices significantly reduce levels of anxiety, depression, and stress, while enhancing overall emotional well-being. This research can support the development of spiritually-based psychological interventions that are more effective in helping individuals achieve better emotional well-being amidst the challenges of modern life.